(untitled) (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to determine the effect of the Silent Demonstration learning model on students’ learning motivation in the Islamic Religious Education (PAI) subject of Taharah material at SMP Negeri 2 Lilirilau, Soppeng Regency. This study uses a quantitative approach with a Quasi Experimental design in the form of Pre-Test Post-Test Control Group Design. The subjects of this study were all seventh grade students of SMPN 2 Lilirilau with a population of 93 students. The sampling technique was carried out randomly, class VII-B with 32 students as the control class and class VII-C with 32 students as the experimental class. The research instrument used was a questionnaire to measure students’ learning motivation. Data analysis includes descriptive statistics and Independent Sample T-test hypothesis testing. The results of the study showed a significant difference from the application of the Silent Demonstration learning model to students’ learning motivation. This is evidenced by the results of the Independent Samples T-test which shows that the application of the Silent Demonstration learning model has an effect on students’ learning motivation in the PAI subject of Taharah material at SMP Negeri 2 Lilirilau, Soppeng Regency